Tilsotolimod: an investigational synthetic toll-like receptor 9 (TLR9) agonist for the treatment of refractory solid tumors and melanoma. (2nd January 2022) - Karime, Christian; Wang, Jing; Woodhead, Gregory; Mody, Kabir; Hennemeyer, Charles T.; Borad, Mitesh J.; Mahadevan, Daruka; Chandana, Sreenivasa R.; Babiker, Hani
ABSTRACT: Introduction: Cancer immunotherapy has seen tremendous strides in the past 15 years, with the introduction of several novel immunotherapeutic agents. Nevertheless, as clinical practice has shown, significant challenges remain with a considerable number of patients responding sub-optimally to available therapeutic options. Research has demonstrated the important immunoregulatory role of the tumor microenvironment (TME), with the potential to either hinder or promote an effective anti-tumor immune response. As such, scientific efforts have focused on investigating novel candidate immunomodulatory agents with the potential to alter the TME toward a more immunopotentiating composition. Areas Covered: Herein, we discuss the novel investigational toll-like receptor 9 agonist tilsotolimod currently undergoing phase II and III clinical trials for advanced refractory cancer, highlighting its mode of action, efficacy, tolerability, and potential future applications in the treatment of cancer. To this effect, we conducted an exhaustive Web of Science and PubMed search to evaluate available research on tilsotolimod as of August 2021. Expert opinion: With encouraging early clinical results demonstrating extensive TME immunomodulation and abscopal effects on distant tumor lesions, tilsotolimod has emerged as a potential candidate immunomodulatory agent with the possibility to augment currently available immunotherapy and provide novel avenues of treatment for patients with advanced refectory cancer.